The Effect of Transportation System on the Economic Growth of the Japanese Economy 1965-2000:using nine region inter-regional IO model - Tsubasa Shibata; Takashi Yano; Hiroyuki Kosaka (European Regional Science Association (ERSA), 2010)
Japan had experienced rapid economic growth since 1960. We can point out that the establishment of better and high-speed transportation was one of the crucial factors for the growth. Hence,,,ÄÄthis paper,,ÄÄexamines historically the impact of the high-speed transport infrastructure developments on Japan's economic growth by employing an inter-regional input-output model for Japanese,,ÄÄeconomy,,ÄÄcovering,,ÄÄnine,,ÄÄregions. This model is based on the IO,,ÄÄtables from 1965 to 2000 in constant prices (nine regions and eight,,ÄÄsectors ) and determines sectoral output and sectoral price simultaneously. For this purpose, evaluation of transport development is quite important. This paper develops an index of transportation evaluation which focuses on the balance between the time-cost and the fare of any high speed transportation. Incorporating this index in the inter-regional input-output model, the,,ÄÄpaper analyzes the effects of transport infrastructure development. As a result, this,,ÄÄpaper found positive relationship between the Japan economic growth and the development of transport system (particularly highway system),,,ÄÄand also found problems associated with economic disparities among regions: i.e., centralization (concentration of people and goods) and decentralization occurred in core and local regions, respectively.
Keywords: 330; international input output model; Japanese economy; Transportations